ON THE HYPERBOLIC FIBONACCI MATRIX FUNCTIONS - Bahsi, M; Solak, S (TWMS journal of applied and engineering mathematics, 2018)
In this study, we will introduce a new class of hyperbolic matrix functions. By comparing Binet formulas for the Fibonacci and Lucas numbers to the formulas of classical hyperbolic matrix functions, we will define hyperbolic Fibonacci matrix functions and we will deal with some of their properties.Keywords: Matrix Function, hyperbolic functions, Fibonacci Numbers.AMS Subject Classification: 15A16, 65F60, 11B39